2018
DOI: 10.1192/bji.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Haiti: is it culturally pathological?

Abstract: Not for the first time in recent history, the people of Haiti have been obliged to fall back on their resilience strategies in the aftermath of Hurricane Matthew. Following the powerful earthquake that struck the country on 12 January 2010, the entire population had to find the resources to survive in the face of extensive material damage and loss of life: over 222 000 dead, more than 300 000 injured and between 4000 and 7000 amputees (UNDP, 2010).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…Our findings align with Ungar (2013) and his argument that “resilience can look like pathological adaptation” (p. 262) if researchers do not engage in understanding young people's clever navigations of threatening social environments. By contrast, our study challenges the suggestion of Haitian resilience as social pathology ( Derivois et al, 2018 ) and nuances previous research on resilience among young people in Haiti, which has mainly been conducted among street-based children ( Cénat et al, 2018 ; Derivois et al, 2020 ; Karray et al, 2016 ). These authors appreciate the complex historical, spiritual, and collective sources of coping and thriving.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Our findings align with Ungar (2013) and his argument that “resilience can look like pathological adaptation” (p. 262) if researchers do not engage in understanding young people's clever navigations of threatening social environments. By contrast, our study challenges the suggestion of Haitian resilience as social pathology ( Derivois et al, 2018 ) and nuances previous research on resilience among young people in Haiti, which has mainly been conducted among street-based children ( Cénat et al, 2018 ; Derivois et al, 2020 ; Karray et al, 2016 ). These authors appreciate the complex historical, spiritual, and collective sources of coping and thriving.…”
Section: Discussioncontrasting
confidence: 90%
“…Regarding Haitians, Rahill et al (2016) similarly called for future research on resilience to pay attention to local Haitian expressions, and their rich culture of proverbs. Derivois et al (2018) highlight a paradox among street children, where "the most vulnerable populations [scoring highest on PTSD and depression symptoms] in Haiti have the highest resilience scores" (p. 79). Consequently, they ask whether Haitian resilience might indicate social or cultural pathology.…”
Section: Idioms Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…But what we really see expressed on their faces is what many Haitians aptly call kriz – that is, ‘an emotional reaction to trauma’ marked by dissociation, loss of consciousness, convulsions, dizziness, and extreme weakness (Beckett, 2013: 41). Derivois et al (2018: 79) posit that the ‘resiliency’ of Haitian natural disaster victims does not ‘imply the absence of trauma’. They suggest that what appears to be Haitian exceptional resilience may actually be ‘pathological resilience’ – that is, ‘a form of resilience that sublimates setbacks and makes it possible to ‘roll with the punches’ without the ability to bounce back in the long term.’ Although the earthquake victims were able to rely on familial, social, and spiritual networks to navigate the earthquake’s aftermath, many survivors naturally experienced long-term post-traumatic stress, depression, and anxiety.…”
Section: Living or Deadmentioning
confidence: 99%
“…The studies of Cénat and Derivois (2014) on polytrauma and the resilience of Haitian street children showed that these child victims of polytrauma demonstrate self-efficacy in coping with their traumatic experiences and less than 15% of them they achieved scores reaching clinical rates of post-traumatic stress disorder. Although various studies (Karray, Joseph et al, 2016;Derivois and Cénat et al, 2018) show that children have a level of resilience ranging from moderate to very high despite their precarious living conditions. Poverty, as Joseph and Derivois (2015) demonstrated to us, is an aggravating factor in violence because it is both more present and more serious in poor families.…”
Section: Introductionmentioning
confidence: 99%